(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Field performance of in vitro plantlets and conventionally propagated potato plants was observed. Five types of mulch viz. no mulch (control), black polythene, white polythene, straw and water hyacinth and six types of potato viz. Diamant conventional (conv.), Cardinal (conv.), Granola (conv.), Diamant plantlet (Plt.), plantlets of Cardinal and Granola were considered in this investigation. Significant effects of variety and mulch were found among the parameters studied. The highest (20.92 t ha-1) yield was recorded from Diamant, followed by Cardinal and the lowest (0.56 t ha-1) yield was obtained from Granola plantlet. Among the five different mulches, the highest (9.19) number of tubers hill-1 was harvested from straw mulch, whereas the lowest (7.35) number of tubers hill-1 was found in no mulch treatment. Straw mulch also gave the highest (10.97 t ha-1) yield than other treatments. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):21-34, 2012